Capillary rise height of sulfate in Portland-limestone cement concrete under physical attack: Experimental and modelling investigation. (January 2022) - Zhang, Zhongya; Zou, Yang; Yang, Jun; Zhou, Jianting
Abstract: Capillary rise is a dominate mechanism for the subsequent salt crystallization damage on concrete structures partially exposed to sulfate bearing environments. The aim of this study is to assess the capillary rise height of sulfate ( h ) in Portland cement (PC) and Portland-limestone cement (PLC) concretes under physical attack. The impacts of limestone contents (0 wt%, 10 wt% and 30 wt%) and water-to-binder ratios (w/b of 0.4 and 0.6) on the pore structures and sorptive property of concrete specimens were investigated. Results show that the effects of limestone content on the capillary rise heights, pore structures and sorptivity of PLC-based concrete specimens differed from different w/b ratios, as a consequence from the competition mechanism between filler effect and dilution effect due to the incorporation of limestone. The heights of efflorescence zone in PLC-based concrete specimens were found to be closely related to their volumes of capillary pores, while those of subflorescence zone only exhibited slight fluctuation at varying compositions. The time-dependent evolution of h can be divided into two stages and almost 35.7%–46.5% of the final height were reached in the first month (the fast increase stage). The capillary rise height h predicted by the modified model demonstrated good agreements with those obtained from experiments, when compared to other prediction models.